End of life vehicles recovery : process descriptio, its impact and direction of research - Mat Saman, Muhamad Zameri; Blount, Gordon N. (Faculty of Mechanical Engineering, 2006)
In recent years, environmental issues and sustainability have become one of the main items of debate in the automotive industries. In relation to that, most countries have set a new legislation because the situation is getting worse especially in the developed country. The legislation forces all the vehicle manufacturers to accept responsibility for the complete life cycle of vehicles. In another words, the vehicle manufacturers are forced by law to take back and recycle their products in order to support product stewardship and to enforce environmentally friendly product life cycles. This paper provides a snapshot of current practices in vehicle recovery in Europe, USA, Japan and Australia together with legislation, stakeholders and markets influencing in industry. The concepts of sustainable development and end-of-life vehicle recovery are discussed. The paper then outlines the factors that must instigate the longer-term changes required to more readily support the core themes of the end-of-life vehicle recovery.